2020
DOI: 10.1186/s12889-020-08587-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between household chaos and child, parent, and family outcomes: a systematic scoping review

Abstract: Background: Household chaos, represented by the level of disorganisation or environmental confusion in the home, has been associated with a range of adverse child and family outcomes. This review aims to (1) identify how household chaos is measured, (2) chart study details of household chaos literature, and (3) map the existing literature with respect to the relationship between household chaos and child, parent, and family outcomes. We expect that this review will highlight the need to consider the importance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
119
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 154 publications
(144 citation statements)
references
References 126 publications
6
119
1
1
Order By: Relevance
“…An important component of preschooler behaviors, particularly sleep and screen-time, is the home environment [ 15 , 16 ]. Accordingly, a risk factor for poor cognitive development [ 17 ] and early childhood obesity [ 18 ] is daily disruptions within the home environment or “household chaos” [ 19 ]. Household chaos encompasses high levels of household unpredictability, noise, and crowding [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…An important component of preschooler behaviors, particularly sleep and screen-time, is the home environment [ 15 , 16 ]. Accordingly, a risk factor for poor cognitive development [ 17 ] and early childhood obesity [ 18 ] is daily disruptions within the home environment or “household chaos” [ 19 ]. Household chaos encompasses high levels of household unpredictability, noise, and crowding [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Note, household chaos refers to the level of disorganisation, noise, and environmental confusion in the home, and has been associated with a range of adverse child outcomes. It has been suggested that household chaos impacts children by increasing levels of stress and distraction, interfering with children’s attention allocation and information processing skills, and compromising positive parent-child interactions and parental responsiveness [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…Household chaos, which represents the level of disorganisation, environmental confusion, and background noise and distractions in the home [ 53 ], was assessed using the 15-item Chaos, Hubbub, and Order Scale (CHAOS) [ 58 ], and engagement in routines of daily life using the Daily Living Routines subscale of the Child Routine Inventory (CRI) [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…While greater levels of chaos are more likely to occur among households with fewer socioeconomic resources [14], chaos is more than a marker for poverty. In studies adjusting for the in uence of socioeconomic status, chaos is consistently identi ed as an independent risk factor for less optimal outcomes of child health and development [14,16]. Young children (≤ 5 years) exposed to greater levels of chaos are more likely to experience poorer cognitive development [17], less school readiness [17], increased behavioral problems [18], and poorer overall health [19], when compared to children living in less chaotic environments.…”
Section: Chaos and Childhood Obesitymentioning
confidence: 99%